Molecular epidemiology of Giardia and Cryptosporidium in dogs and cats in Chiang Mai, Thailand - Tangtrongsup, Sahatchai, author; Salman, Mo, advisor; Lappin, Michael, advisor; Ballweber, Lora, committee member; Reif, John, committee member (Colorado State University. Libraries, 2013)
Giardia duodenalis and Cryptosporidium spp. are the common causes of diarrhea in humans and animals, including domestic and wildlife, throughout the world. The species complex G. duodenalis and the genus Cryptosporidium consist of host-adapted and zoonotic genotypes/species. Companion animals, especially dogs and cats, can be infected by the host-adapted as well as the zoonotic genotype/species of these organisms. Therefore, these animals have been questioned regarding their potential to serve as reservoirs for human transmission. In this dissertation, an epidemiological study of Giardia and Cryptosporidium as well as the molecular characterization of these organisms in dogs and cats in Chiang Mai, Thailand was completed. A greater understanding of the prevalence and risk factors associated with Giardia and Cryptosporidium infection can aid veterinarians in the control and prevention of these important diseases. Furthermore, the potential for zoonotic transmission will be reduced. In Chapter 1, Giardia and Cryptosporidium and its epidemiology in dogs and cats are reviewed as well as an update on the situation regarding giardiasis and cryptosporidiosis in Thailand. In Chapter 2, a preliminary study to determine the prevalence of Giardia and Cryptosporidium infection in dogs and cats in Chiang Mai, Thailand is described. Fecal samples were collected for two months (July and August, 2008). The genotype/species of these two organisms were determined as well as the risks associated with infection such as age, sex, diarrhea status, housing type and the presence of co-infection of Cryptosporidium (for Giardia infection) or the presence of Giardia in the case of Cryptosporidium infection. It was shown that Giardia and Cryptosporidium infections were common in dogs in Chiang Mai and that dogs could be a potential reservoir for zoonotic transmission to humans. In Chapter 3, the larger cross-sectional study is described. Samples were collected a year later from August 2009 to February 2010. The objectives were to determine the effect of seasonality (wet months or rainy vs. dry months or winter), to determine the potential risk factors associated with Giardia and Cryptosporidium infections, as well as to determine the genotype/species of these organisms. The results suggested that Giardia infection in dogs was prevalent in the rainy season, whereas seasonality was not significantly associated with Cryptosporidium infection. Young dogs, dogs living in crowded settings, dogs having diarrhea or chronic diarrhea, and dogs shedding Cryptosporidium oocysts had a high risk for Giardia infection. Risk factors associated with Cryptosporidium infection in dogs were age less than one year and dogs having diarrhea. Giardia duodenalis assemblage A and C. parvum were identified in this study; however, the potential role in zoonotic transmission could not be determined. Chapter 4 presents a brief report on the comparison of sugar and sedimentation concentration techniques prior to immunofluorescent assay to detect Giardia cysts and Cryptosporidium oocysts. Concentration of fecal samples may enhance the detection of cysts and oocysts. However, in frozen samples the spherical structure of Giardia cysts or Cryptosporidium oocysts may be affected by the freeze-and-thaw process; therefore, the use of sugar concentration technique may not appropriate for frozen fecal samples. Chapter 5 compares the PCR assays using different target genes in detecting Giardia and Cryptosporidium in dogs and cats from Chiang Mai, Thailand. Three PCR assays for Giardia were compared, including the PCR targeting to glutamate dehydrogenase (gdh), triose phosphate isomerase (tpi), and β-giardin gene. Three PCR assays for Cryptosporidium, a heat shock protein targeting PCR and two PCR assays to detect SSU-rRNA (one step PCR vs nested PCR assays), were compared. Giardia gdh and Cryptosporidium one-step SSU-rRNA PCR assays had the highest amplification rates. Using a multilocus analysis approach, most of the Giardia isolates were dog genotypes, whereas 30%-40% of Cryptosporidium species were C. parvum. This finding may suggest a potential role of zoonotic transmission of Cryptosporidium from dogs and cats in this region of Thailand. The research described in this dissertation raises the knowledge in the field of canine and feline giardiasis and cryptosporidiosis. The results provide additional prevalence and risk analysis results for dogs and cats in Chiang Mai, Thailand. The molecular analyses suggest that the use of multilocus analysis is superior to using only one locus. In addition, the results also suggest that sugar flotation was not appropriate as a concentrating method for frozen fecal material and that sedimentation should be used when freezing of the sample is necessary.
Keywords: cryptosporidium; molecular characterization; giardia; cats; dogs; Thailand